Sekolah dengan konsep pendidikan humanis - Sabaruddin, Sabaruddin (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2020)
Education is a shared duty and responsibility to develop awareness and insight between humans to continue life. Efforts to increase awareness, children's personality, and develop creativity gave birth to an educational approach called "humanization" in the current educational process. Efforts are needed to create humanist schools to create a diverse world of education for students and teachers alike. Humanist education has the concept that humans, as subjects, can face the world and their environment, as well as the ability to overcome and solve problems that will be faced by humans themselves. Humanist school is a school that loves and gives freedom in creativity according to students' interests and talents. The humanist curriculum's goal must be dynamic personal development, integrity, and autonomy, healthy personality attitudes to the environment. Teachers, as initiators, motivators, and facilitators, carry out learning to solve students' problems or social problems. Students understand their potential to develop their potential positive and minimize negative self-potential.